Predicting Periarticular Infection in Children With Septic Arthritis of the Hip: Regionally Derived Criteria May Not Apply to All Populations. Issue 5 (May 2019) - Refakis, Christian A.; Arkader, Alexandre; Baldwin, Keith D.; Spiegel, David A.; Sankar, Wudbhav N.
Abstract : Background: The management of septic arthritis of the hip in children can be complicated by the presence of additional coexisting periarticular infections (PAIs). Criteria predicting the presence of PAI have recently been proposed by Rosenfeld and colleagues with the goal of using magnetic resonance imaging (MRI) efficiently in the workup of septic arthritis. The purpose of this study was to determine the applicability of recently published predictive criteria for PAI (developed in the Southwestern United States using a variety of joints) to septic arthritis of the hip treated at a large Northeastern tertiary care center. Methods: We studied patients treated for septic arthritis of the hip with irrigation and debridement in a large Northeastern tertiary care center over a 10-year period. Laboratory and clinical variables related to presentation, treatment, and outcome were collected. Subjects with and without a perioperative MRI were compared with published criteria by Rosenfeld and colleagues. Results: Fifty-one subjects (53 hips) were identified with a mean age of 7.0 years (range, 1.2 to 19.3 y) and mean follow-up was 16 months (range, 2 to 85 mo). MRIs were obtained in 20 subjects (43%). Coexisting osteomyelitis was revealed in 7/20 of these studies (35% of MRIs); 4 of which showed coexisting intramuscular abscesses. Within our MRI cohort, the Rosenfeld criteria were found to have a sensitivity of 86%, a specificity of 54%, and a false-positive rate of 50% for the hip (compared with originally reported sensitivity of 90%, specificity of 67%, and false-positive rate of 33%). Overall, advanced imaging changed management in 5/51 patients (9%) by influencing the need for further treatment, whereas the remainder underwent isolated treatment of the septic hip joint with no adverse outcomes. One patient in the MRI cohort (without PAI) developed osteonecrosis of the femoral head. Conclusions: We found lower sensitivity and specificity and higher false-positive rates for the Rosenfeld criteria in the hip for our geographically distinct population. Using the Rosenfeld criteria, MRIs would have been ordered unnecessarily in half of our series. Because of potential differences in regional microbiology and anatomic-specific factors, general predictive criteria for coexisting PAI based a single geographic region may be less generalizable to cases of hip sepsis in other geographic areas such as the Northeastern United States. Level of Evidence: Level 4—retrospective cohort study.